Etika Bisnis dalam Perlindungan Data Pribadi Konsumen di Era Bisnis Digital: dalam Studi Literatur - Khairani Alawiyah Matondang; Tia Handani; Annisa Handayani; Fidia Wati (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
The rapid digital transformation has fundamentally altered contemporary business operational paradigms and generated crucial issues regarding the security of customers' personal information. This study explores the implementation of ethical principles in the business world, particularly concerning the protection of consumer personal information within the digital economy context, employing a systematic literature review methodology. Information gathering was conducted through comprehensive examination of scholarly publications discussing business morality, information confidentiality in the digital realm, and personal data security by applying qualitative research methodology. The findings reveal that customer personal information has transformed into a strategic commodity with high economic value within the digital business ecosystem, while simultaneously triggering substantial security threats such as information security breaches, identity theft, and irresponsible data exploitation. Although Indonesian regulations have been established through Law Number 27 of 2022 concerning Personal Data Protection and the Electronic Information and Transactions Law, their implementation continues to face numerous obstacles including jurisdictional limitations over international business entities, minimal digital literacy among the public, and the complexity of artificial intelligence technology that presents contemporary privacy threats. This research concludes that business morality in personal data protection is not merely a juridical obligation, but also a fundamental investment strategy for building consumer credibility and sustainable business continuity in the long term. The practical implications of this research underscore the urgency of cross-stakeholder collaboration in realizing a credible and secure digital ecosystem.